Human resource development in the Value Added Tax(VAT) Service : (a case study of the VAT Secretariat in Accra) - Gyawu, Elizabeth Achiaa (2011)
A thesis submitted to the Department of Economics and Industrial Management, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Business Administration (MBA) degree.